Witch Queen rising - Stephens, Savannah (Stephens, Savannah. Blood & magic duology., 2026)
"A reclusive witch who fled the burden of her bloodline rises to be the greatest among them in this lush and haunting fantasy debut. For New Orleans witchkin, there is no greater honor than to become the Prime-chosen to rule. But the title is meant to pass between two rival Houses of magic. Not to the prodigal daughter of the former Prime who died under mysterious circumstances. As a girl, Seraphine Barreau was dubbed the Tick Witch for her ability to feed on magic and make it her own. Even among those who alter fate and manipulate reality, she was a powerful outcast feared and misunderstood by her people. Now dragged back to continue the legacy that nearly destroyed her, Phine has her work cut out for her. She must earn the respect of her people, navigate the politics of the paranormal communities residing in her city, and heal a broken heart all the while battling a parasitic curse poisoning witchkin. Between her werewolf ex, power-hungry vampires, and the skeletons in her family's closet, Phine must learn to make peace with her past to save her-and all of witchkin's-future"-- Provided by publisher.